Effectiveness of the STAD-Type Cooperative Learning Model Assisted by Baamboozle Game to Improve Students’ Cognitive Learning Outcomes - Khayyirah, Shilvi; Islami, Nur; Zulhelmi, Zulhelmi (Journal of Educational Sciences, 2024)
This study aims to determine the effectiveness of Cooperative learning model type STAD assisted by baamboozle game to improve students’ cognitive learning outcomes. The type of research used is quasi-experimental using Posttest Only Nonequivalent Control Group Design. The population of this study were 254 students of class VIII SMP N 30 Padang. The samples of this study were students of class VIII H as the experimental class and students of class G as the control class. The data collection instrument used was the posttest of students’ cognitive learning outcomes in the subject of effort and energy. The results of the data obtained were processed using descriptive analysis and inferential analysis. The results showed that the STAD type cooperative learning model assisted by baamboozle game was effective to improve students’ cognitive learning outcomes, as evidenced by the difference in students’ cognitive learning outcomes between the experimental and control classes.